Digital Divide, Digital Equity, and Online Learning Engagement Among Selected College Students in Pamantasan ng Cabuyao - Caparas, Shienna Marie; Yango, Antonio (Technium Social Sciences Journal, 2023)
Hybrid-flexible learning, also known as HyFlex, is an instructional approach that combines flexible course structure and hybrid learning. This allows students the option to attend class sessions in person or online. The purpose of this study was to assess the Digital Divide, Digital Equity, and Online Learning Engagement Among Selected College Students in Pamantasan ng Cabuyao. This attempted to measure the respondents’ level of the digital divide, digital equity, and online learning engagement, and test their significant relationship. The findings showed that the respondents’ level of the digital divide is very high, the level of digital equity is high and the level of online learning engagement is also high. Hypothesis testing revealed that the level of the digital divide and digital equity are the drivers of online learning engagement. This study is regarded as a helpful resource in bridging the digital divide and promoting digital equity and online learning engagement.